An Ex vivo Apoptotic and Cytotoxic Effects of Frankincense on Oral Squamous Cell Carcinoma Cell Line - Mostafa, Sarah; El-Bolok, Amr Helmy Moustafa; Fahmi, Ahmed Nabil; Alaaeldin, Enas (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Oral squamous cell carcinoma is accounting for almost 90% of oropharyngeal cancer diagnoses. Natural herbal medicine can use as an alternative, or complementary, or adjunctive for cancer treatment. Frankincense and its combination with myrrh have anticancer effects on different cancer types. METHODS: In this research, aqueous and methanolic extracts of frankincense and the combination of aqueous extract of frankincense and myrrh were applied on tongue squamous cell carcinoma cell line to study their cytotoxic and apoptotic effect by the assessment of cell viability and cytotoxicity, caspase 3 and 8 activation, reactive oxygen species activity, mitochondrial membrane potential, morphological changes, and nuclear area factor measurements. RESULTS: The result showed that aqueous and methanolic extracts of frankincense have cytotoxic and apoptotic effects in a concentration-dependent manner with an IC50 value of 21.05 ± 1.27 μM for aqueous extract, 36.72 ± 2.07 μM for methanolic extract, and IC50 value of 1.31 ± 0.04 μM for combination of aqueous extract of frankincense and myrrh extract after 24 h. CONCLUSION: Different extracts of frankincense and the combination of aqueous extract of frankincense and myrrh extract exhibited cytotoxic and apoptotic effects by reducing the cell viability and activating caspases 3 and 8 causing intrinsic- and extrinsic-mediated apoptosis pathways activation with the involvement of oxidative stress that was conceivable with cytonuclear morphological alterations results.